Jurnal Teknik Menyusui yang benar pada Ibu Nifas di Klinik Pratama Ar-Rabih Tahun 2021 - Wenti Sintia Mutiara Sianturi; Rina Yulviana (Jurnal Kebidanan Terkini (Current Midwifery Journal), 2022)
Breastfeeding is an unrivaled way of providing ideal food for the healthy growth and development of babies. Often the breastfeeding process fails, especially in primigravida postpartum mothers. This can be due to the lack of knowledge of mothers about the correct breastfeeding technique. For that a mother needs someone who can guide her in terms of breastfeeding. This case report aims to provide midwifery care to postpartum mothers who still lack knowledge about correct breastfeeding techniques so that postpartum mothers do not experience problems breastfeeding their babies. The case study was carried out at the Ar-Rabih Primary Clinic and then continued with care at the patient's home. Midwifery care for Mrs. S is carried out starting from 07 May 2021 to 09 June 2021. The visit is carried out for 2 times. The method of documentation in the form of SOAP. This case study was conducted on primigravida postpartum women. From the results of this Final Project, it was obtained that the postpartum mother at the first visit still did not know the correct breastfeeding technique but after the author provided midwifery care regarding the correct breastfeeding technique, the postpartum mother finally understood and understood the correct breastfeeding technique. Likewise, on the second visit conducted by the author, it was found that the postpartum mother had no complaints about the correct breastfeeding technique and had been able to apply it when breastfeeding her baby. It is recommended to BPM or Midwifery Clinic to pay more attention to counseling about correct breastfeeding techniques, so that postpartum mothers can understand and practice it. Keywords : Breastfeeding Techniques, Postpartum mothers